Hot-dip galvanized aluminum magnesium steel with excellent adhesive force and manufacturing method of hot-dip galvanized aluminum magnesium steel

By optimizing the composition and process in the substrate and plating solution, the corrosion resistance and adhesion problems of zinc-aluminum-magnesium plating in harsh environments are solved, and the zinc-aluminum-magnesium plating with high corrosion resistance and excellent adhesion is achieved, which expands the Application scope.

CN119433365AActive Publication Date: 2025-02-14武汉钢铁有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411355069.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

When used in harsh environments, the existing zinc-aluminum-magnesium coating has insufficient corrosion resistance and poor adhesion, which limits its application range.

Method used

By designing low Si and low Mn components in the substrate and adding high magnesium aluminum components to the plating solution, the mass ratio of Al/Mg and Al/Si is controlled to improve the adhesion and corrosion resistance of the plating layer.

Benefits of technology

The zinc-aluminum-magnesium plating layer that improves corrosion resistance while maintaining excellent adhesion is achieved, expanding its application range in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433365A_ABST
    Figure CN119433365A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hot-dip galvanized aluminum magnesium steel, and discloses hot-dip galvanized aluminum magnesium steel with excellent adhesive force and a manufacturing method thereof, a substrate of the hot-dip galvanized aluminum magnesium steel comprises the following chemical components in percentage by mass: 0.05-0.07% of C, 0.05-0.20% of Si, 0.3-0.5% of Mn, 0.025-0.055% of Als, 0.025-0.035% of P, less than or equal to 0.010% of S, 0.01-0.02% of Nb, and the balance of Fe and other inevitable impurities; the plating layer on the substrate comprises the following chemical components in percentage by mass: 12.0-25.0% of Al, 4.0-10.0% of Mg, 0.06-0.5% of Si, 0.01-0.2% of Ca, the mass ratio of Al to Mg is greater than or equal to 2.5, the mass ratio of Al to Si is 50-160, and the balance of Zn and other inevitable impurities. The substrate adopts a low-Si and low-Mn component design to ensure the adhesiveness of a plating layer, the mechanical property is enhanced through P and Nb, a plating solution adopts a high-magnesium and high-aluminum component design to ensure high corrosion resistance, and the texture of the plating layer and the composition and form of an interface reaction layer between the plating layer and the substrate are controlled through the Al / Mg mass ratio and the Al / Si mass ratio to improve the adhesion of the plating layer, so that the corrosion resistance of the plating layer is improved. Therefore, the corrosion resistance and the adhesive force are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-dip galvanized aluminum-magnesium steel materials, and in particular relates to a hot-dip galvanized aluminum-magnesium steel material with excellent adhesion and a manufacturing method thereof. Background Art

[0002] Zinc-aluminum-magnesium coating has been the main development direction of high corrosion-resistant coatings in the past 20 years. "Chalco" zinc-aluminum-magnesium coating (Al content 3-11%) products add appropriate amounts of Al and Mg to traditional zinc-based coatings, and their corrosion resistance is 3-5 times higher than that of pure zinc coating products (GI). In agricultural facilities, industrial buildings, road facilities, photovoltaic brackets and other industries, "Chalco" zinc-aluminum-magnesium coating products are accelerating the replacement of traditional zinc-based coatings. At present, the Mg content of "Chalco" zinc-aluminum-magnesium coating products that are widely used in the market does not exceed 3%. For the demand for materials in harsh environments, such as photovoltaic projects in coastal or high humidity and high temperature areas, fishery and animal husbandry facilities, urban underground pipe corridors, and building facilities in industrial areas, the corrosion resistance of coating products needs to be further improved on the basis of traditional zinc-aluminum-magnesium coatings.

[0003] By further increasing the content of Al and Mg, the corrosion resistance of the coating can be further improved. However, the increase in the content of Al and Mg will cause changes in the microstructure of the coating and the reaction layer. Compared with zinc-aluminum-magnesium coating products with low Mg content (Mg content <3%), the content of the hard and brittle compound phase MgZn2 increases, and MgZn2 will mainly be generated and grown before the final multi-electroctic reaction to form a larger block MgZn2 phase. The increase in Al content will lead to an increase in the temperature of the plating solution, and due to the violent reaction of Al and Fe, the control of the reaction layer between the coating and the steel base is more complicated. In addition, the increase in Al and Mg content will lead to an increase in zinc ash and zinc slag. These factors will have an adverse effect on the adhesion of the coating, thereby affecting the processing performance of the coating product. For example, for processing with a small deformation, it may be qualified, and for processing with a large deformation, the risk of coating shedding is high, which limits the application range of such high corrosion-resistant products. Therefore, while improving the corrosion resistance of the coating, excellent adhesion can be obtained, which plays an important role in increasing the usable range of the product. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a hot-dip galvanized aluminum-magnesium steel with excellent adhesion and a manufacturing method thereof in view of the deficiencies in the prior art. The substrate is designed with low Si and low Mn components to ensure the adhesion of the coating, and the mechanical properties are enhanced by P and Nb. The plating solution is designed with high magnesium-aluminum components to ensure high corrosion resistance, and the structure of the coating and the composition and morphology of the interface reaction layer between the coating and the substrate are controlled by the Al / Mg mass ratio and the Al / Si mass ratio to improve the adhesion of the coating, thereby taking into account both corrosion resistance and adhesion.

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a hot-dip galvanized aluminum-magnesium steel material with excellent adhesion, including a substrate and a coating attached to the surface of the substrate.

[0006] In the above scheme, the chemical composition of the substrate includes, by mass percentage: C: 0.05-0.07%, Si: 0.05-0.20%, Mn: 0.3-0.5%, Als: 0.025-0.055%, P: 0.025-0.035%, S≤0.010%, Nb: 0.01-0.02%, and the remainder is Fe and other inevitable impurities.

[0007] In the above solution, the thickness of the substrate is 0.4 to 2.5 mm.

[0008] In the above scheme, the chemical composition of the coating includes, by mass percentage: Al: 12.0-25.0%, Mg: 4.0-10.0%, Si: 0.06-0.5%, Ca: 0.01-0.2%, and the Al / Mg mass ratio is ≥2.5, the Al / Si mass ratio is 50-160, and the remainder is Zn and other inevitable impurities.

[0009] In the above scheme, the single-sided adhesion amount of the coating is 40 to 300 g / m 2 .

[0010] In the above scheme, the structure of the coating includes primary crystal (Al) phase, blocky MgZn2 phase encapsulating (Al) phase, blocky (Zn) phase, Mg2Si phase, and multi-element eutectic Al / Zn / MgZn2 structure.

[0011] In the above scheme, there is an interface reaction layer between the coating and the substrate, which is a dense, approximately equiaxed granular Al-Fe compound, which is covered with a Ca-containing compound.

[0012] In the above scheme, the yield strength of the hot-dip galvanized aluminum-magnesium steel is ≥380MPa, the tensile strength is ≥450MPa, and the elongation is ≥25%.

[0013] The present invention also provides a method for manufacturing a hot-dip galvanized aluminum-magnesium steel material with excellent adhesion, comprising the following steps:

[0014] 1) After molten iron is smelted, it is refined and thin slabs are continuously cast to obtain ingots;

[0015] 2) After the ingot is heated, it is hot rolled, cooled, coiled and leveled to obtain a hot-rolled raw material coil;

[0016] 3) The hot-rolled raw material coil is pickled and cold-rolled to obtain a substrate;

[0017] 4) After the substrate is annealed in the annealing furnace, it is put into the zinc pot for hot-dip galvanizing aluminum and magnesium, and then taken out of the pot for cooling to obtain hot-dip galvanized aluminum and magnesium steel with excellent adhesion.

[0018] In the above scheme, the continuous casting speed is 4.5-5.0 m / min, and the thickness of the cast billet is 60-85 mm.

[0019] In the above scheme, the ingot is pre-descaled before soaking, and the descaling pressure is 140-180 bar.

[0020] In the above scheme, the furnace entry temperature of the cast billet for equalization is 850-950°C, the heating time is 25-40 minutes, and the furnace exit temperature is 1130-1180°C.

[0021] In the above scheme, the ingot is descaled by high-pressure water before hot rolling, and the descaling pressure is 280-380 bar.

[0022] In the above scheme, the controlled rolling speed of the hot rolling is 7-13 m / s, and the final rolling temperature is 780-820°C.

[0023] In the above scheme, the coiling temperature is 500-580°C, and the steel coil temperature is reduced to below 50°C before being leveled. The thickness of the obtained hot-rolled raw material coil is 2.0-6.0 mm.

[0024] In the above scheme, the temperature of the pickling acid solution is controlled at 80-90°C.

[0025] In the above scheme, the total reduction ratio of the cold rolling is 58-80%.

[0026] In the above scheme, the substrate is first heated to 760-800°C at a rate of 10-50K / s in the annealing furnace, kept warm for 2-200s, and then cooled at a rate greater than 10K / s to a temperature 10-15°C higher than the plating solution temperature in the zinc pot.

[0027] In the above scheme, the hydrogen concentration in the annealing furnace is ≥10%, the dew point is ≤-35°C, and the dew point of the furnace nose is -15 to -5°C.

[0028] In the above scheme, the temperature of the plating solution in the zinc pot is 40-50° C. higher than the melting point of the coating.

[0029] In the above scheme, during the cooling process after being taken out of the pot, the average cooling rate of the coating from the beginning of solidification to the end of solidification is greater than 30K / s.

[0030] The design idea of ​​the substrate components in the present invention is:

[0031] In order to improve the adhesion of the coating, a low Si and low Mn composition design is adopted in the selection of alloy elements of the substrate. However, low Si and Mn contents cannot guarantee that the strength reaches the target value. If the annealing temperature is lowered to introduce an incomplete recrystallized structure to improve the strength, this will cause the elongation to be significantly reduced and fail to reach the target value of 25%. In addition, a lower annealing temperature is not conducive to the reduction of residual iron oxide on the surface of the strip. The residual iron oxide will affect the wetting of the plating solution on the steel base surface and cause defects such as leakage plating or dezincification during processing. Therefore, in order to adopt a higher annealing temperature that can effectively reduce the residual iron oxide on the surface of the strip and ensure that the strength reaches the target at this temperature, a small amount of P and Nb are added to the composition. The content of the main alloying elements is controlled as follows:

[0032] C: C is the main strengthening element in steel. C dissolves in ferrite and forms carbides to increase the strength of steel. The higher the C content, the higher the strength of the steel, but the plasticity and toughness decrease. Since the peritectic zone must be avoided in the thin slab continuous casting and rolling CSP process, the present invention controls the C content to 0.05-0.07%.

[0033] Si: Si is a commonly used deoxidizer in steelmaking. Si does not form carbides, but dissolves in ferrite, which can improve the strength of steel. However, too high Si content will significantly reduce the plasticity, toughness and welding performance of steel. At the same time, Si tends to be enriched on the surface of steel plates, which will affect the wetting of the plating solution on the steel base surface and cause poor adhesion. In order to further improve the adhesion of the coating, the present invention controls the Si content to 0.05-0.20%.

[0034] Mn: Mn is an excellent deoxidizer and desulfurizer in steelmaking. Mn can reduce the hot brittleness of steel caused by sulfur, thereby improving the hot working properties of steel. Mn is dissolved in ferrite to improve the strength of steel. At the same time, Mn tends to be enriched on the surface of the steel plate, which will affect the wetting of the plating solution on the steel base surface and cause the problem of poor adhesion. In order to further improve the adhesion of the coating, the present invention controls the Mn content to 0.3-0.5%.

[0035] P: In order to control the surface oxidation of the substrate during the annealing process, the present invention controls the Si and Mn elements to a relatively low level. In order to ensure the strength of the steel, an appropriate amount of P is added. P can significantly strengthen ferrite through solid solution strengthening, but too much P will cause plasticity and significantly reduce impact toughness, especially at low temperatures, making the steel significantly brittle. The present invention controls the P content range to 0.025-0.035%.

[0036] Nb: A small amount of Nb is added to steel mainly to improve the yield strength and tensile strength by utilizing its precipitation strengthening and fine grain strengthening effects. Among them, fine grain strengthening does not lead to a decrease in elongation. Too low a content of Nb will not have a significant strengthening effect, and too much Nb will lead to an increase in alloy cost. Considering the tensile performance target of the present invention, the Nb content is controlled at 0.01-0.02%.

[0037] The coating composition is designed as follows:

[0038] Al: The increase of Al content can improve the corrosion resistance of the coating. When the Al content increases, the melting point of the coating will increase overall, and the temperature of the zinc liquid needs to be increased accordingly during production. Compared with the zinc liquid with low aluminum content, the zinc slag and zinc ash will increase significantly. When the Al content is greater than 25%, as the Al content increases, the plane corrosion resistance of the coating increases slowly, and the incision corrosion resistance decreases. Therefore, the Al content in the coating of the present invention is controlled to be 12-25%.

[0039] Mg: The increase of Mg content in the coating promotes the rapid generation of dense corrosion products containing Zn, Al, and Mg on the surface of the coating, which is beneficial to the protection of the inside of the coating and the substrate. The corrosion products are fluid and can protect the incision. However, the increase of Mg content will lead to the increase of compound phase MgZn2, and the MgZn2 phase generated before the final multi-electroctic reaction will increase significantly. These blocky hard and brittle MgZn2 are easy to crack during processing, leading to dezincification problems. Therefore, the Mg content in the coating of the present invention is controlled to be 4.0-10.0%.

[0040] Al / Mg mass ratio: In order to improve the adhesion of the coating while ensuring high corrosion resistance, the growth of the MgZn2 phase needs to be controlled. First, the MgZn2 phase should be prevented from being a primary phase, and second, the blocky MgZn2 phase in the coating structure should be wrapped with the tough (Al) phase, thereby inhibiting the expansion of cracks formed in the MgZn2 phase. This requires controlling the ratio of Al and Mg content. Therefore, the content ratio of Al and Mg in the coating of the present invention is controlled to be not less than 2.5.

[0041] Si: The main function of the trace element Si in the plating solution is to control the growth of the Fe-Al reaction layer at the interface between the substrate and the coating, which is very important for the adhesion of the coating. Si can not only effectively inhibit the corrosion of Al on the substrate in the high-temperature plating solution, but also inhibit the excessive growth of the interface reaction layer. Too little Si cannot effectively play a controlling role on the interface reaction layer, and too much Si cannot be completely dissolved in the plating solution, and more Si-containing compounds will be generated and attached to the substrate or in the coating, thereby affecting the adhesion of the coating. Therefore, the Si content in the coating of the present invention is controlled to be 0.06-0.5%.

[0042] Al / Si mass ratio: Al / Si mass ratio is very important for controlling the morphology of the Al-Fe reaction layer and the compounds on the interface. Too high Al / Si mass ratio is not conducive to the formation of dense granular Fe-Al compounds similar to equiaxed ones. Too low Al / Si ratio will cause excess Si to form a large amount of Si-containing compounds with elements such as Al\Mg at the interface between the coating and the substrate, which is not conducive to the bonding between the coating and the substrate. Therefore, the content ratio of Al and Si is controlled at 50-160.

[0043] Ca: Due to the high Al and Mg content in the plating solution, more Al and Mg oxides will be generated on the surface of the plating solution. These oxides are loose and porous and cannot prevent further oxidation of the plating solution. When the strip enters the plating solution, the Al and Mg oxides will adhere to the substrate or the coating, thereby affecting the adhesion of the coating. Ca and oxygen can generate dense oxides, thereby preventing further oxidation of the plating solution and effectively reducing the Al and Mg oxides on the surface of the plating solution. Too much Ca cannot be completely dissolved in the plating solution, and will form various compounds with elements such as Al, Mg and Si, and adhere to the substrate or the coating, thereby reducing the adhesion of the coating. Therefore, the present invention controls the Ca content to 0.01-0.2%.

[0044] The design idea of ​​the manufacturing process in the present invention is:

[0045] In order to improve the adhesion of the coating, it is very important to clean the surface of the substrate before plating and control the hot-dip process. The manufacturing process mainly considers the control of iron oxide scale during heating and hot rolling of the ingot, cleaning of iron oxide scale during pickling, reduction of residual iron oxide scale on the surface of the strip during hot-dip, control of zinc slag and zinc ash at the zinc pot, control of plating solution temperature and cooling rate after plating. Compared with conventional hot-rolled ingots, the surface iron oxide scale of the CSP process ingot is thinner, and it is difficult to form an iron oxide scale block of moderate thickness so that it can be removed during descaling. Therefore, the process should be controlled during the heating stage of the ingot to form an iron oxide scale block of moderate thickness on the surface of the ingot, which is conducive to subsequent high-pressure water descaling. In addition, compared with conventional hot-rolled ingots, CSP slabs are thinner. For the same finished product thickness, the compression ratio is relatively small, and the surface roughness is compressed in equal proportion, which is larger than that of conventional hot-rolled slabs. Therefore, in order to improve the surface quality of the substrate, a larger reduction rate of 58-80% is used in the cold rolling process after pickling, thereby further improving the surface quality. In terms of bath composition design, due to the high Al and Mg content, there will be more zinc slag and zinc ash during production, which will affect the quality of the coating. In production, nitrogen humidification is used in the furnace nose to control the zinc ash, and the bath temperature is controlled to control the zinc slag. The main process controls are as follows:

[0046] Pre-descaling of the ingot before entering the furnace: The ingot is pre-descaled before entering the furnace to remove the protective slag and large-sized iron oxide scale blocks on the surface of the ingot. The pre-descaling pressure is set to 140-180 bar in the present invention.

[0047] Ingot heating time and furnace discharge temperature: During the heating process, iron oxide scale will be generated on the surface of the ingot. Too thick or too thin iron oxide scale is not conducive to high-pressure water descaling. In the present invention, the ingot heating time is set to 25-40 minutes, and the furnace discharge temperature is set to 1130-1180°C. Under this heating time and temperature, iron oxide scale blocks with moderate thickness are formed on the surface of the ingot, which is conducive to subsequent high-pressure water descaling.

[0048] High-pressure water descaling before hot rolling: High water pressure is beneficial to removing the iron oxide scale formed on the surface of the ingot during the heating process. The high-pressure water descaling pressure is set to 280-380 bar in the present invention.

[0049] Hot rolling final rolling temperature: A lower final rolling temperature can reduce the generation of secondary iron scale on the surface of the steel coil during the cooling process after rolling. The present invention sets the final rolling temperature to 780-820°C. Too high a temperature will lead to more secondary iron scale during cooling, and too low a temperature will lead to excessive ferrite during rolling, thereby reducing the strength of the final product.

[0050] Coiling temperature: A lower coiling temperature is beneficial to suppress the generation of tertiary iron scale during the air cooling process of the steel coil after coiling. The present invention sets the coiling temperature to 500-580°C. Too high a temperature will cause more tertiary iron scale to be generated during cooling, while too low a temperature will exceed the cooling capacity of the cooling unit, and the risk of the coil head tilting during the coiling process is high, thereby affecting production.

[0051] Pickling temperature: The present invention sets the pickling temperature to 80-90°C. Within this temperature range, the hot-rolled substrate can fully remove the iron oxide scale without over-pickling. If the temperature is too high, the substrate surface will be corroded while removing the iron oxide scale, and if the temperature is too low, the iron oxide scale will not be fully removed.

[0052] Annealing temperature: Annealing temperature not only determines the mechanical properties, but is also very important for the cleanliness of the strip surface. At a higher annealing temperature, the iron oxide scale remaining on the strip surface after pickling can be effectively reduced. The surface iron activity after reduction is higher, and the reaction with the plating solution is stronger, which is beneficial to the adhesion of the coating. Since a small amount of P and Nb is added to the composition design of the substrate of the present invention, although the content of Si and Mn is low, there is no need to increase the strength by lowering the annealing temperature. Therefore, the present invention sets the annealing temperature to 760-800°C. Too high an annealing temperature will reduce the strength of the steel, and too low an annealing temperature will result in the inability to effectively reduce the iron oxide scale on the strip surface.

[0053] Hydrogen concentration in the annealing furnace: In order to enhance the reduction of residual iron oxide on the surface of the strip and improve the efficiency of gas heat transfer in the furnace, the hydrogen concentration must be controlled at no less than 10%. Too low a hydrogen concentration will not be able to effectively reduce the residual iron oxide on the surface of the strip, resulting in surface defects such as exposed iron and zinc slag on the coating surface during the hot-dip process, which is not conducive to the adhesion of the coating.

[0054] Dew point in annealing furnace: In order to inhibit the oxidation of strip steel in the annealing furnace, the dew point in the furnace needs to be controlled at -35°C or below. Too high a dew point will cause local oxidation on the surface of the strip steel, resulting in surface defects such as exposed iron and zinc slag on the coating surface during the hot-dip process, which is not conducive to the adhesion of the coating.

[0055] Furnace nose dew point: In order to reduce the impact of zinc vapor volatilized from the liquid surface in the furnace nose on the substrate, nitrogen humidification is used at the furnace nose to control the dew point at the furnace nose to -15 to -5 ° C. Too low a dew point cannot effectively suppress the zinc ash formed on the zinc liquid surface.

[0056] Bath temperature: The melting point of the coating system is related to the composition. Too high a bath temperature will increase defects such as zinc ash and zinc slag on the coating surface, which is not conducive to the adhesion of the coating. Therefore, the bath temperature of the present invention is set to be 40 to 50°C higher than the melting point of the coating.

[0057] Cooling rate after plating: Due to the increase of Al and Mg content, the solidification interval of the coating will increase significantly, so the solidification time will be prolonged. Too long cooling time will cause the size of the MgZn2 phase to be too large, which is not conducive to the adhesion of the coating. Therefore, the cooling rate after plating of the present invention is set to be greater than 30K / s.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] (1) The present invention provides a high corrosion-resistant zinc-aluminum-magnesium coated steel plate with excellent adhesion, whose yield strength is ≥380MPa, tensile strength is ≥450MPa, elongation is ≥25%, and thickness specification can be as low as 0.4mm. The product is suitable for facilities in coastal areas or high humidity and high temperature areas, as well as factory areas.

[0060] (2) Based on the design of substrate and coating composition and process control, the corrosion resistance is improved by increasing the Al and Mg content of the coating, while ensuring excellent coating adhesion, which can be used for processing with large deformation.

[0061] (3) The manufacturing process uses CSP hot rolling and cold rolling hot-dip galvanized aluminum and magnesium. The CSP process can not only provide thin-gauge raw material coils, which helps the cold rolling production line to produce high-strength and thin-gauge products, but also the CSP process can effectively shorten the process flow and reduce energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1This is the coating structure picture of Example 6.

[0063] Figure 2 This is a picture of the interface reaction layer of Example 6.

[0064] Figure 3 This is a picture of Ca compounds on the interface reaction layer of Example 6 and an energy spectrum component analysis diagram.

[0065] Figure 4 This is a picture of the coating structure of Comparative Example 6.

[0066] Figure 5 This is a picture of the interface reaction layer of Comparative Example 7.

[0067] Figure 6 This is a picture of the interface reaction layer of Comparative Example 8. DETAILED DESCRIPTION

[0068] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0069] In the following examples and comparative examples, the chemical compositions of the substrates used include 5 kinds, as shown in Table 1.

[0070] Table 1 Chemical composition of substrate

[0071] Substrate No. C(%) Si(%) Mn(%) Nb(%) Als(%) P(%) S(%) 1 0.06 0.05 0.42 0.012 0.025 0.025 0.008 2 0.05 0.12 0.30 0.01 0.031 0.035 0.007 3 0.07 0.2 0.50 0.020 0.055 0.031 0.008 4 0.07 0.13 0.42 0.006 0.032 0.029 0.009 5 0.06 0.15 0.36 0.015 0.037 0.007 0.007

[0072] In the following examples and comparative examples, the chemical compositions of the coating used include 10 kinds, see Table 2.

[0073] Table 2 Chemical composition and melting point of coating

[0074]

[0075] In the following embodiments, a method for manufacturing a hot-dip galvanized aluminum-magnesium steel material with excellent adhesion comprises the following steps:

[0076] 1) After molten iron is smelted, it is refined and thin slabs are continuously cast at a continuous casting speed of 4.5-5.0 m / min to obtain a cast slab with a thickness of 60-85 mm;

[0077] 2) The ingot is pre-descaled at a descaling pressure of 140-180 bar; then the ingot is heated in a furnace at a temperature of 850-950°C, a heating time of 25-40 min, and a furnace-out temperature of 1130-1180°C; the ingot is descaled by high-pressure water at a descaling pressure of 280-380 bar; then hot rolling is performed at a controlled rolling speed of 7-13 m / s and a final rolling temperature of 780-820°C; after hot rolling, the ingot is cooled to 500-580°C for coiling, and then the temperature of the steel coil is reduced to below 50°C and leveled to obtain a hot-rolled raw material coil with a thickness of 2.0-6.0 mm;

[0078] 3) The hot-rolled raw material coil is pickled, and the acid solution temperature is controlled at 80-90° C.; then cold-rolled, and the total cold-rolling reduction rate is 58-80% to obtain a substrate, and the substrate thickness is 0.4-2.5 mm;

[0079] 4) The substrate enters the annealing furnace, firstly heated to 760-800℃ at a rate of 10-50K / s, kept warm for 2-200s, and then cooled to 10-15℃ higher than the plating solution temperature in the zinc pot at a rate greater than 10K / s; the hydrogen concentration in the annealing furnace is ≥10%, the dew point is ≤-35℃, and the dew point of the furnace nose is -15--5℃; then it enters the zinc pot for hot-dip galvanizing aluminum and magnesium, and the plating solution temperature in the zinc pot is 40-50℃ higher than the melting point of the coating; during the air cooling process after exiting the pot, the average cooling rate of the coating from the beginning of solidification to the end of solidification is greater than 30K / s, and hot-dip galvanized aluminum and magnesium steel with excellent adhesion is obtained.

[0080] In the following examples and comparative examples, 17 specific process conditions are used, as shown in Tables 3 to 5.

[0081] Table 3 Parameters of continuous casting, soaking and hot rolling

[0082]

[0083] Table 4 Related parameters of hot rolling, pickling and cold rolling

[0084]

[0085]

[0086] Table 5 Parameters of annealing furnace annealing and zinc pot hot dip galvanizing aluminum and magnesium

[0087]

[0088] Table 6 shows the substrate composition, coating composition and process conditions used in each embodiment and comparative example. In order to better compare the effect, the coating thickness of the test samples is 120g / m on one side. 2, the effects of each embodiment and comparative example were tested. Among them, the corrosion resistance is reflected by the CCT plane red rust resistance cycle, and the test refers to the standard JASO M609-91. The specific test conditions are: one cycle of 8 hours; 2 hours of salt spray, using 5% NaCl solution, temperature 35°C; then 4 hours of drying at 60°C, relative humidity 20-30%; then 2 hours of wetting, temperature 50°C, relative humidity 95%; cycle the above steps until red rust appears; the cycle from the start of the experiment to the appearance of red rust is taken as the CCT plane red rust resistance cycle. 0T bending and 1T bending are used to test whether the coating is cracked or detached to reflect the adhesion of the coating. If there is no cracking or detachment, it is qualified by √, and if there is cracking or detachment, it is unqualified by ×.

[0089] Table 6 Specific conditions and results of each embodiment and comparative example

[0090]

[0091]

[0092] It can be seen from Table 6 that the hot-dip galvanized magnesium-aluminum steels obtained in various embodiments of the present invention all exhibit good mechanical properties and corrosion resistance, and the coating has excellent adhesion. Figure 1 This is the coating structure diagram of Example 6. It can be seen from the figure that the structure of the coating includes primary crystal (Al) phase, blocky MgZn2 phase encapsulating (Al) phase, blocky (Zn) phase, Mg2Si phase, and multi-element eutectic Al / Zn / MgZn2 structure, wherein the blocky MgZn2 phase encapsulates the (Al) phase, and the tough (Al) phase helps to inhibit the expansion of MgZn2 cracks; Figure 2 This is the interface reaction layer of Example 6. As can be seen from the figure, it is a dense, nearly equiaxed granular Al-Fe compound. Figure 3 These are the pictures of Ca-containing compounds on the interface reaction layer of Example 6 and the energy spectrum component analysis diagram. The white plus signs in the left figure indicate the Ca-containing compounds, and the energy spectrum component analysis also confirms the existence of the Ca-containing compounds.

[0093] In Comparative Examples 1 and 2, since the Nb or P content in the substrate components is low, the yield strength of the obtained steel material is significantly reduced. Figure 4 This is the coating structure diagram of comparative example 3. It can be seen from the figure that when the Al / Mg mass ratio is too low, part of the MgZn2 phase is generated separately, the adhesion is reduced, and dezincification occurs in the 0T bend; Figure 5 This is the interface reaction layer of Comparative Example 4. It can be seen from the figure that when Al / Si is too high, the reaction layer of Al and Fe is columnar particles, the adhesion decreases, and dezincification occurs in the 0T bend; Figure 6It is the interface reaction layer of comparative example 5. It can be seen from the figure that when the Al / Si mass ratio is too low, the excess Si will generate a large number of Si-containing particles on the interface reaction layer between the coating and the substrate, the adhesion is reduced, and dezincification occurs in the 0T bending; in comparative example 6, due to the low Ca content, sufficient dense oxides containing Ca cannot be formed on the surface of the plating solution to inhibit further oxidation of the plating solution, and more Al and Mg oxides will be generated on the surface of the plating solution. These oxides will adhere to the substrate or the coating, thereby reducing the adhesion of the coating, and dezincification occurs in the 0T bending; in comparative example 7, due to the high Ca content, excessive Ca cannot be completely dissolved in the plating solution, and various compounds are formed with elements such as Al, Mg and Si, which are attached to the substrate or the coating, thereby reducing the adhesion of the coating, resulting in failure of both the 0T and 1T bending tests.

[0094] Comparative Example 8 shows that when the pre-descaling pressure before entering the furnace is too low, the protective slag or large pieces of iron oxide scale on the surface of the ingot cannot be effectively removed. The protective slag or iron oxide scale remaining on the substrate surface is not conducive to hot-dip galvanizing, affecting the adhesion of the coating after hot-dip galvanizing. Comparative Example 9 shows that when the heating time is too short, the surface of the ingot cannot form an iron oxide scale block of moderate thickness, which is not conducive to the subsequent high-pressure water descaling. The iron oxide scale remaining on the substrate surface is not conducive to hot-dip galvanizing, affecting the adhesion of the coating after hot-dip galvanizing. Comparative Example 10 shows that when the ingot out of the furnace temperature is too high, the primary iron oxide scale is thick, and the subsequent high-pressure water descaling cannot be completely removed, resulting in a thick iron oxide scale remaining on the substrate surface, which cannot be completely removed in the subsequent process, affecting the adhesion of the coating after hot-dip galvanizing. Comparative Examples 11 and 12 show that when the final rolling temperature is too high or the coiling temperature is too high, excessive secondary or tertiary iron oxide scale will be generated, which cannot be completely removed in the subsequent process, which will reduce the adhesion of the coating after hot-dip galvanizing. Comparative Example 13 shows that when the pickling temperature is too low, the acid solution cannot effectively dissolve the scale oxide on the surface of the substrate, and the residual scale oxide will reduce the adhesion between the coating and the substrate. Comparative Example 14 shows that when the annealing temperature is too low, the scale oxide remaining on the surface of the strip cannot be effectively reduced to iron, which will affect the wetting of the plating solution on the substrate during the hot-dip process, thereby reducing the adhesion of the coating. Comparative Example 15 shows that when the hydrogen concentration is too low, the scale oxide on the surface of the substrate cannot be effectively reduced, and the residual scale oxide will reduce the adhesion between the coating and the substrate. Comparative Example 16 shows that when the dew point in the annealing furnace is too high, the surface of the strip will be locally oxidized, affecting the wetting of the plating solution on the substrate during the hot-dip process, thereby reducing the adhesion of the coating. Comparative Example 17 shows that when the dew point of the furnace nose is too low, the atmosphere there cannot effectively suppress the zinc ash formed on the zinc liquid surface, and the zinc ash attached to the substrate will reduce the adhesion between the coating and the substrate. Comparative Example 18 shows that when the bath temperature is too high, the amount of zinc ash and zinc slag increases significantly, and the zinc slag remaining in the coating will reduce the adhesion of the strip. Comparative Example 19 shows that when the cooling rate after plating is too low, the size of the generated blocky MgZn2 phase will become larger, and it is easy to crack during bending deformation, reducing the adhesion of the coating.

[0095] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A hot-dip galvanized aluminum-magnesium steel material with excellent adhesion, characterized in that: It includes a substrate and a coating attached to the surface of the substrate; The chemical composition of the substrate includes, by mass percentage, C: 0.05-0.07%, Si: 0.05-0.20%, Mn: 0.3-0.5%, Als: 0.025-0.055%, P: 0.025-0.035%, S≤0.010%, Nb: 0.01-0.02%, and the balance is Fe and other inevitable impurities; the chemical composition of the coating includes, by mass percentage, Al: 12.0-25.0%, Mg: 4.0-10.0%, Si: 0.06-0.5%, Ca: 0.01-0.2%, and the Al / Mg mass ratio is ≥2.5, the Al / Si mass ratio is 50-160, and the balance is Zn and other inevitable impurities.

2. The hot-dip galvanized aluminum-magnesium steel material with excellent adhesion according to claim 1, characterized in that: The thickness of the substrate is 0.4-2.5 mm; the single-sided adhesion of the coating is 40-300 g / m 2 .

3. The hot-dip galvanized aluminum-magnesium steel material with excellent adhesion according to claim 1, characterized in that: The microstructure of the coating includes a primary (Al) phase, a blocky MgZn2 phase encapsulating an (Al) phase, a blocky (Zn) phase, a Mg2Si phase, and a multi-element eutectic Al / Zn / MgZn2 microstructure.

4. The hot-dip galvanized aluminum-magnesium steel material with excellent adhesion according to claim 1, characterized in that: There is an interface reaction layer between the coating and the substrate, which is a dense, approximately equiaxed granular Al-Fe compound covered with a Ca-containing compound.

5. The hot-dip galvanized aluminum-magnesium steel material with excellent adhesion according to claim 1, characterized in that: The yield strength of the hot-dip galvanized aluminum-magnesium steel is ≥380MPa, the tensile strength is ≥450MPa, and the elongation is ≥25%.

6. The method for producing a hot-dip galvanized aluminum-magnesium steel material with excellent adhesion according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) After molten iron is smelted, it is refined and thin slabs are continuously cast to obtain ingots; 2) The ingot is pre-descaled and then put into the furnace for equalization, the furnace temperature is 850-950°C, the heating time is 25-40min, and the furnace temperature is 1130-1180°C; the ingot out of the furnace is descaled by high-pressure water, and then hot rolled, and the final rolling temperature is 780-820°C; after hot rolling, it is cooled to 500-580°C for coiling, and then the temperature of the steel coil is reduced to below 50°C and then leveled to obtain a hot-rolled raw material coil; 3) The hot-rolled raw material coil is pickled, and the acid solution temperature is controlled at 80-90° C.; then cold-rolled, and the total cold-rolling reduction rate is 58-80% to obtain a substrate; 4) The substrate enters the annealing furnace, first heated to 760-800℃ for insulation, and then cooled to 10-15℃ higher than the plating solution temperature in the zinc pot; the hydrogen concentration in the annealing furnace is ≥10%, the dew point is ≤-35℃, and the dew point of the furnace nose is -15--5℃; then it is put into the zinc pot for hot dip, and cooled out of the pot to obtain hot dip galvanized aluminum-magnesium steel with excellent adhesion.

7. The method for manufacturing hot-dip galvanized aluminum-magnesium steel with excellent adhesion according to claim 6, characterized in that: The descaling pressure of the pre-descaling is 140-180 bar; the descaling pressure of the high-pressure water descaling is 280-380 bar.

8. The method for manufacturing hot-dip galvanized aluminum-magnesium steel with excellent adhesion according to claim 6, characterized in that: The heating rate of the substrate in the annealing furnace is 10-50K / s, the insulation time after heating is 2-200s, and the cooling rate after insulation is greater than 10K / s.

9. The method for manufacturing hot-dip galvanized aluminum-magnesium steel with excellent adhesion according to claim 6, characterized in that: The plating solution temperature in the zinc pot is 40-50° C. higher than the melting point of the coating; during the cooling process after the coating is taken out of the pot, the average cooling rate of the coating from the beginning of solidification to the end of solidification is greater than 30K / s.

10. The method for manufacturing hot-dip galvanized aluminum-magnesium steel with excellent adhesion according to claim 6, characterized in that: The continuous casting speed is 4.5-5.0 m / min, and the thickness of the obtained cast billet is 60-85 mm; the controlled rolling speed of the hot rolling is 7-13 m / s, and the thickness of the obtained hot-rolled raw material coil is 2.0-6.0 mm.

Citation Information

Patent Citations

  • High-corrosion-resistance hot-dip galvanized aluminum magnesium high-strength steel and manufacturing method thereof

    CN117327992A

  • High strength hot-dip galvanized steel sheet excellent in plating adhesion and formability, and manufacturing method therefor

    JP2013076137A

  • Plated steel material

    WO2024185849A1

  • KR20190077202A